Building health consciousness in the future orientation of the challenge of health education - Izabella Maria Łukasik (Lubelski Rocznik Pedagogiczny, 2019)
Based on health promotion programmes and strategies, it can be observed that the majority of the proposed measures should be aimed at preventive efforts taken before any health or epidemiological issues arise. It must be emphatically stressed that health awareness among the Poles is low, and, for this reason, lifestyle diseases, for instance, are often diagnosed at the later stages, when advanced changes have already started. This is also the reason why health education is of vital importance, especially in terms of improving health awareness. A short questionnaire entitled Health Consciousness in the Future Orientation Perspective has been prepared. This questionnaire can be applied as a screening tool to help identify individuals with low health awareness, and thus facilitate the practice of more effective educational activities. The questionnaire includes 18 items which focus on the three main areas: 1) the search for and application of health-related information, and the trend towards a healthy lifestyle and health vigilance; 2) the responsibility for taking care of one’s own health in the present and in future times; 3) the motivation to lead a healthy lifestyle as an individual tendency towards healthy behaviour, aimed at health problem prevention and health condition improvement. The reliability of the scale was determined on the basis of Cronbach’s alpha, in which the value of alpha was 0.874, and the values of the specific scales were I – 0.836, II – 0.838, III-0.601.